Pancasila Sebagai Dasar Negara Kesatuan Republik Indonesia Perspektif Al-Qur’an : Analisis Hermeneutika Hans Georg Gadamer - Sunardi Sunardi (CV. ULIL ALBAB CORP, 2024)
This article describes the values ​​of Pancasila from the perspective of the Qur'an and this paper uses Gadamer's